2005
DOI: 10.1177/0093650205279350
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Presumed Media Influence on Women’s Desire to Be Thin

Abstract: This study investigated the effect of magazine use on the desire to be thin within the theoretical framework of presumed influence. Structural equation modeling supported the hypothesis that reading beauty and fashion magazines increased the drive for thinness both directly and indirectly. The indirect pathway included the perceived prevalence of the thin ideal in mass media, the presumed influence of the thin ideal on others, and the perceived influence of the thin ideal on self. Social pressure to be thin ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(82 citation statements)
references
References 54 publications
4
71
0
6
Order By: Relevance
“…It is perhaps this third person effect, the tendency to believe that others are more affected by media than oneself (Davison 1983;Perloff 2009), coupled with the negative effect that perceived peer appearance norms have on body satisfaction (Bair et al 2014;Krcmar et al 2008;Lin et al 2015), that contributes to findings of interactions between perceptions of peers' appearance norms and media influence. Specifically, it has been found that the beliefs of women that others were influenced by media to prefer a thinner body size were associated with participants' own desire to be thin DOES MEDIA LITERACY MITIGATE RISK 7 (Park 2005). Mock peer comments about models' body size paired with thin-ideal images on a YouTube page were found to influence adolescent girls' post-exposure body dissatisfaction (Veldhuis et al 2014).…”
Section: Image Processing: Peer Appearance Normsmentioning
confidence: 99%
“…It is perhaps this third person effect, the tendency to believe that others are more affected by media than oneself (Davison 1983;Perloff 2009), coupled with the negative effect that perceived peer appearance norms have on body satisfaction (Bair et al 2014;Krcmar et al 2008;Lin et al 2015), that contributes to findings of interactions between perceptions of peers' appearance norms and media influence. Specifically, it has been found that the beliefs of women that others were influenced by media to prefer a thinner body size were associated with participants' own desire to be thin DOES MEDIA LITERACY MITIGATE RISK 7 (Park 2005). Mock peer comments about models' body size paired with thin-ideal images on a YouTube page were found to influence adolescent girls' post-exposure body dissatisfaction (Veldhuis et al 2014).…”
Section: Image Processing: Peer Appearance Normsmentioning
confidence: 99%
“…Furthermore, reading beauty and fashion magazines help to develop the drive for thinness (Levine & Murnen, 2009;Park, 2005). To support these studies on media exposure, one experimental study found that when female college students were exposed to 16 magazine pages featuring thin-ideal female body shapes for five days in a row, their body dissatisfaction increased significantly throughout the time period of the study (Knobloch-Westerwick & Crane, 2012).…”
Section: How Important Are Media Characters To You? Fiementioning
confidence: 99%
“…The effect of thin-idealized images in the mass media on body image has been well debated in numerous studies (e.g., Fardouly, Diedrichs, Vartanian, & Halliwell, 2015;Park, 2005;Sheldon, 2010). These studies suggest that media has a significant influence on body dissatisfaction and body-esteem (Sheldon, 2010) and that the idealized images provided in mass media reinforce the importance of physical appearance in women's lives (Vartanian, Giant, & Passino, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…No es de extrañar, por tanto, que se haya encontrado un vínculo significativo entre la recepción mediática de determinados programas o la participación en determinados foros de Internet y enfermedades como la bulimia o la anorexia (Botta, 1999;Harrison y Cantor, 1997;Harrison, 2000;Harper y Tiggemann, 2008;Park, 2005;Tiggemann, 2006). Al mismo tiempo, muchas prácticas que comienzan a ser habituales -como la liposucción, la cirugía estética y otras operaciones quirúrgicas-son fruto de las imposiciones sociales vehiculadas por la publicidad y por los medios de comunicación masiva.…”
Section: Cuerpo Y Medios De Comunicaciónunclassified